2013
DOI: 10.1590/1414-431x20132882
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin and adrenotensin regulate collagen synthesis and proliferation in pulmonary arterial smooth muscle cells

Abstract: To understand the pathophysiological mechanisms of pulmonary arterial smooth muscle cell (PASMC) proliferation and extracellular-matrix accumulation in the development of pulmonary hypertension and remodeling, this study determined the effects of different doses of adrenomedullin (ADM) and adrenotensin (ADT) on PASMC proliferation and collagen synthesis. The objective was to investigate whether extracellular signal-regulated kinase (ERK1/2) signaling was involved in ADM- and ADT-stimulated proliferation of PAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This result indicates that ADT and ΔADT are able to stimulate the proliferation of endothelial cells, and suggests that ΔADT has a higher proliferation rate than ADT. In addition, this finding is consistent with reports showing the effects of ADT on upregulated proliferation in rat mesangial cells and pulmonary arterial smooth muscle cells (19,20).…”
Section: δAdt Stimulates Angiogenesis In Cultured Hrmvecsupporting
confidence: 92%
“…This result indicates that ADT and ΔADT are able to stimulate the proliferation of endothelial cells, and suggests that ΔADT has a higher proliferation rate than ADT. In addition, this finding is consistent with reports showing the effects of ADT on upregulated proliferation in rat mesangial cells and pulmonary arterial smooth muscle cells (19,20).…”
Section: δAdt Stimulates Angiogenesis In Cultured Hrmvecsupporting
confidence: 92%
“…It acts systemically and in autocrine and paracrine fashion [54,55], exerting or mediating vasodilatory, natriuretic, diuretic, antioxidative, anti-inflammatory, antimicrobial, and metabolic effects [42,50,[56][57][58]. Upregulated by hypoxia, inflammatory cytokines, bacterial products, and shear stress, ADM has in preclinical and animal models been shown to reduce hypoxic pulmonary vascular structural remodeling and fibrosis and to inhibit bronchoconstriction; the molecule also has been shown to stabilize barrier function in the lungs by downregulating pro-inflammatory factors and reactive oxidative species [42,50,51,[59][60][61][62]. Circulating ADM elevation, e.g., in end-stage pulmonary disease [63], is believed to reflect "high demand" for these compensatory/counter-regulatory effects [28,42].…”
Section: Adm and Proadmmentioning
confidence: 99%
“…When observing experimental studies, adrenomedullin has been suggested to inhibit proliferation in pulmonary artery smooth muscle cells and to alleviate pulmonary artery collagen accumulation in PH. [13][14][15] Many reports have also shown that adrenomedullin administration attenuates PH in animal models, and that adrenomedullin may improve hemodynamics in human PH. [9][10][11][12][13] In the present study, we also report that plasma renin protein levels in PAH are elevated compared to controls and unaltered versus CTEPH patients, but lower compared to left heart failure regardless of PH presence.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Adrenomedullin has also been shown to inhibit proliferation in pulmonary artery smooth muscle cells and to alleviate pulmonary artery collagen accumulation in PH. [13][14][15] Besides adrenomedullin, the processing of the adrenomedullin precursor also yields pro-adrenomedullin N-20 terminal peptide (PAMP), which also acts as a vasodilator, as well as the mid-regional pro-adrenomedullin (MR-proADM). 16 Reliable measurement of adrenomedullin and PAMP may be difficult.…”
Section: Introductionmentioning
confidence: 99%